The Role of Ethics in Character Building Learners - Sihombing, Iin Nur Indrayani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Globalization accompanied by extraordinary advances in science and technology has opened up the world completely. Man is inseparable from his daily life. In this situation, a person will discover and even experience firsthand every change that occurs in his life. This world that provides an open opportunity certainly provides an opportunity for many people to start something new. Things like this can have both positive and negative impacts, but this tendency tends to have a bad impact on young people. By observing the phenomena that occur a lot today, our country is experiencing a moral decline. This moral decline results from the loss of character of a person. The application of ethics is one of the solutions to shape the character of students. Ethics is a science of decency and goodness that governs how human beings should behave in society. The purpose of this scientific paper is to find out what are the roles of ethics in shaping the character of students and to find out how the application of ethics in shaping the character of students. The results of this study show that ethics plays an important role in the formation of the character of students. A student can have good character if he is taught ethics in his life. Ethics directs students to always do good to those around them, be it in the school environment or in the community.